Functionalised acrylic microgels as reactive toughness modifiers of epoxy resins - Machotová, Jana; Svoboda, Ladislav; Šňupárek, Jaromír; Večeřa, Miroslav; Prokůpek, Luboš (University of Pardubice, 2015)
The effect of glycidyl-functionalised acrylic microgels incorporated into a commercial waterborne dispersion of epoxy resin and a solvent-free low molecular weight epoxy resin, respectively, on mechanical properties of cured materials is described in this paper. The objective of this study was to show the usefulness of prepared reactive microgels as toughness modifiers. It has been found that the incorporation of microgel particles influenced positively both the toughness performance and the other mechanical properties of tested epoxies without affecting significantly their thermal properties.